In vitro antiproliferative activity of uncommon xanthones from branches of Garcinia achachairu. (1st September 2016) - Mariano, Luisa Nathália Bolda; Vendramini-Costa, Débora Barbosa; Ruiz, Ana Lúcia Tasca Gois; de Carvalho, João Ernesto; Corrêa, Rogério; Cechinel Filho, Valdir; Delle Monache, Franco; Niero, Rivaldo
Abstract: Context Garcinia achachairu Rusby (Clusiaceae) popularly known as 'achachairu' is used in folk medicine to treat rheumatism, inflammation, pain and gastric disorder. Objective The present study investigated the chemical profile and antiproliferative effects of the methanolic extract, fractions and two xanthones, against some carcinoma cell lines in vitro . Materials and methods The compounds were isolated and identified by chromatographic and spectroscopic methods. The extract, fractions and compounds were tested human tumour cell lines of U-251 (glioma), MCF-7 (breast), NCI/ADR-RES (ovary expressing multi-drug resistance phenotype), 786-0 (kidney), NCI-H460 (lung, non-small cells), PC-3 (prostate) and HT-29 (colon), non-tumour cell line HaCat (human keratinocytes) in doses of 0.25–250 μg mL − 1 for 48 h. The antiproliferative activity was determined by spectrophotometric quantification (at 540 nm) of the cellular protein content using sulphorhodamine B assay. The prediction of parameters involved in the molecular bioavailability was executed directly by ChemDoodle (version 5.0.1) software (iChemLabs, LLC, Somerset, NJ). Results 3-Demethyl-2-geranyl-4-prenylbellidypholine (1 ) and 1, 5, 8-trihydroxy-4′, 5′-dimethyl-2 H -pyrane (2, 3:3, 2)-4-(3-methylbut-2-enyl) xanthone (2 ), gartanin (3 ) and stigmasterol (4 ) were identified on the basis of spectroscopic techniques. Compounds1 and2 exhibited cytocidal activity, especially against breast, prostate and kidney cell lines, with TGI values of 15.8, 4.9, 9.1 and 39.4, 44.7, 40.9 μg/mL, respectively. Discussion and conclusion The presence of two sets of hydrophobic and hydrophilic groups in separate domains in each molecule might play a role in the mediation of tumour-specific action. Our data show that G. achachairu have potent antiproliferative action and should be considered an important source of potent anticancer compounds.